Distribution and Succession of Microbial Communities Along the Dispersal Pathway of Hydrothermal Plumes on the Southwest Indian Ridge - Li, Jiangtao; Yang, Jingyu; Sun, Mingxue; Su, Lei; Wang, Hu; Gao, Jianqi; Bai, Shijie (Frontiers in Marine Science, 2020)
The distribution and succession of microbial communities along the dispersion path of hydrothermal plumes has not been well investigated. In this study, we collected several types of samples from the Longqi hydrothermal field located on the Southwest Indian Ridge, including hydrothermal plumes at different stages of formation, a suite of water column samples across the non-buoyant hydrothermal plumes above this field, and a background seawater column approximately 350 km away from the hydrothermal field. Using CH4 concentration anomalies, three non-buoyant plume samples between 2,535 m and 2,735 m were identified within the water column. Microbial community compositions within these plumes and background seawater samples were examined based on the 16S rRNA genes and revealed significant variations and successions in community composition between different portions of the hydrothermal plumes. Near the vent orifice, representing the initial stage of plume formation, microbial populations were characterized by abundant and diverse putative vent-associated communities including (hyper)thermophiles such as Aquificaceae and Hydrogenothermaceae within the phylum Aquificae, and some epsilonproteobacterial chemolithoautotrophs such as Sulfurovum, Sulfurimonas, and Caminibacter. By contrast, in the rising buoyant plumes and adjacent seawaters, most vent-associated microbial taxa were still present but made only minor contributions to community composition. Some microbial taxa that are common in seawater columns such as alphaproteobacterial Sphingomonadaceae and SAR11 clade, deltaproteobacterial SAR324 clade, and gammaproteobacterial Pseudomonas, together with Sulfurimonas and SUP05 clade, became predominant. Members within the Sulfurimonas and SUP05 clade flourished with considerable abundance in the non-buoyant plumes, although these plumes were mainly composed of alphaproteobacterial Rhodobacteraceae, gammaproteobacterial Alteromonadaceae and Saccharospirillaceae putatively derived from the surrounding ambient seawater. We also analyzed archaeal components in the initial discharge and rising buoyant plume stages, with both primarily consisting of thaumarchaeal Nitrosopumilales and euryarchaeal Marine Group II. Our results indicated that being characteristic microbial lineages within the hydrothermal plumes of the Southwest Indian Ridge, both Sulfurimonas and SUP05 clade display a common and abundant distribution across the plume path. However, out of these clades, Sulfurimonas is more abundant and widespread.